Current transport properties of (Au/Ni)/HfAlO3/n-Si metal–insulator–semiconductor junction. (January 2021) - Arslan, Engin; Badali, Yosef; Aalizadeh, Majid; Altındal, Şemsettin; Özbay, Ekmel
Abstract: In this study, HfAlO3 ternary alloy thin film was grown on n-type silicon using the atomic layer deposition method. The current transport mechanisms in the (Au/Ni)/HfAlO3 /n-Si junction were examined over a wide temperature range (80–360 K). The values obtained for the ideality factor ( n ) varied from 22.93 to 3.94 and the barrier height at zero bias ( Ф B0 ) ranged from 0.221 eV to 0.821 eV as the temperature changed from 80 to 360 K. The Φ B0 –n and Φ B0 –q /2 kT characteristics were investigated to explain the higher n values and non-ideal behavior of the Richardson curves. Two linear regions were found at low temperatures (LTs; 80–180 K) and high temperatures (HTs; 200–360 K), which indicated the presence of a Gaussian distribution barrier height and the average barrier heights ( Φ ‾ B 0 ) were identified. The values obtained for Φ ‾ B o were 0.734 eV for LTs and 1.125 eV for HTs, and the values of σ s were 0.085 V for LTs and 0.140 V for HTs. The values obtained for N ss decreased as the temperature increased and they varied between ~10 12 and 10 13  eV −1  cm −2 . Finally, the dielectric behavior and conductivity of the (Au/Ni)/HfAlO3 /n-Si junction were investigated at frequencies between 5 kHz and 2 MHz at room temperature. The values determined for ε′ and ε′′ at −1 V and 5 kHz were 2.1 and 3.53, respectively. Highlights: Atomic ratio of Hf relative to Al to O very close to 1:1:3 in HfAlO3 thin film. Different current transport mechanisms corresponded to low and high temperatures. Double Gaussian distribution model described current transport mechanisms. Thermionic field emission, field emission, and multistep tunneling not valid. Values obtained for N ss decreased as the temperature increased.